An Unedited Homily on the Sunday of the Myrrh-bearing Women by the Patriarch of Constantinople Kallistos I - Gârbacea, Radu (Sacris Erudiri, 2024)
Abstract This article presents the first edition and an English translation of the homily on the Sunday of the Myrrh-bearing Women by patriarch Kallistos I († 20 June 1364), which has survived in the most important manuscript witnesses of his homiletic work, the codices Athous Chilandar 8 (Lambros 229) and Athous Panteleimonos 1074. The accompanying commentary discusses the text’s date of composition and primary sources.